Assessing the Efficacy of Treatment Modalities in the Context of Adult Drug Courts in Four Jurisdictions in the United States, 1997-2002 - Anspach, Donald F. ([Verlag nicht ermittelbar], 2004)
This study examined adult drug treatment courts. Drug treatment courts are intended to reduce the recidivism of drug-involved offenders by changing their drug-use habits. These courts provide a connection between the criminal justice and treatment systems by combining treatment with structured sanctions and rewards. Researchers collected data between February 2001 and May 2002 on drug court participants, treatment services and staff, and organizations involved in drug court operations in four jurisdictions: Bakersfield, California, Jackson County, Missouri, Creek County, Oklahoma, and St. Mary Parish, Louisiana. Part 1, Retrospective Participant Data, contains recidivism and treatment data on 2,357 drug treatment court participants who were enrolled in one of the drug courts between January 1997 and December 2000. Part 2, Treatment Observation Data, contains data collected from observations of treatment sessions at each site from May through July 2001. Part 3, Staff Survey Data, provides data obtained through surveys of 54 treatment service staff members.